Explaining Interest Group Density Across Economic Sectors: Evidence from Germany. (May 2019) - Klüver , Heike; Zeidler, Elisabeth
Why does the number of interest groups vary across economic sectors? Interest groups are an important channel through which companies can transmit their policy preferences to decision-makers. However, empirical research shows that the number of interest groups varies considerably across sectors. We argue that the size and the wealth of the potential constituency as well as government activity positively affect interest group density. We test our theoretical expectations based on an unprecedented longitudinal analysis of interest groups that registered at the German Bundestag from 1978 until 2013 and show that the number of firms, the wealth of an economic sector, and government activity positively influence interest group density. However, we also find that the relationship between interest groups and legislative activity is reciprocal as legislative activity positively impacts the number of interest groups in an economic sector, but at the same time interest group density also positively affects legislative activity.